THE DESIGN OF A SMART CITY SONIFICATION SYSTEM USING A CONCEPTUAL BLENDING AND MUSICAL FRAMEWORK, WEB AUDIO AND DEEP LEARNING TECHNIQUES - Roddy, Stephen (My University, 2021)
This paper describes an auditory display system for smart city data for Dublin City, Ireland. It introduces and describes the different layers of the system and outlines how they operate individually and interact with one another. The system uses a deep learning model called a variational autoencoder to generate musical content to represent data points. Further data-to-sound mappings are introduced via parameter mapping sonification techniques during sound synthesis and post-processing. Conceptual blending and music theory provide frameworks, which govern the design of the system. The paper ends with a discussion of the design process that contextualizes the contribution, highlighting the interdisciplinary nature of the project, which spans data analytics, music composition and human-computer interaction.
The 26th International Conference on Auditory Display (ICAD 2021)
Keywords: Human-computer interaction; Music theory; Conceptual blending; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Inclusive Society; Making Ireland; Smart & Sustainable Planet; Telecommunications; Auditory Display; Internet of Things; MACHINE LEARNING; Smart Cities; Sonification; Culture; Social services, interventions and supports